Load-transfer mechanism of distribution beams in giant rectangular concrete-filled steel tubular columns. (October 2022) - Luo, Jinhui; Gao, Shuyu; Zhang, Yuanzhi; Guo, Xiaonong; Chen, Shaozhen; Ding, Feng
Abstract: This study investigates the load-transfer mechanism of a distribution beam and the load-bearing capacity of a huge rectangular concrete-filled steel tubular (RCFST) column through experiments and numerical analyses. Axial compression tests on six giant RCFST columns with a scale factor of 1/5 were conducted. Test results indicated the following: 1) All specimens exhibited excellent ductility and failed by local buckling of the steel tube. The distribution beam experienced shear failure because of the large plastic deformation at both beam ends. 2) The distribution beam effectively improved the ultimate load capacity of the specimen and the concrete core. 3) The yield load of the concrete core was approximately twice the shear capacity of the distribution beam, and its ultimate load capacity was slightly higher than twice the tensile capacity of the distribution beam. Subsequently, corresponding scaled finite element models were established and verified by comparison with the experimental results regarding failure modes, load-bearing capacity, and load–displacement curves. Based on the verified finite element models, numerous parametric analyses were conducted on full-scale RCFST columns, considering different section sizes of steel tubes and distribution beams, as well as layouts of the distribution beam. Based on the experimental and numerical analyses of the load-transfer mechanism of the distribution beam, a simplified design formula for the distribution beam was proposed. Highlights: The load-transfer mechanism of distribution beams in RCFST columns were investigated. Axial compression tests on 1/5-scale RCFST columns were conducted. All test specimens showed excellent ductility and failed by local buckling of the steel tube. The distribution beam effectively improved the ultimate load capacity. A simplified design formula for the distribution beam was proposed.